ANALISA PERANCANGAN KURSI KULIAH YANG ERGONOMI - Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2010)
Student can be told have learnt, if internal condition and process the condition of student have with stimulus of environment learn, and is final  activity of study of the student happened change of behaviour. One of the environmental component learn perceived in this research is scheme of lecture chair to reach freshmen, effective and. Anthropometry represent the part of ergonomic which peculiarly study body, covering linear dimension, weight, content, size measure, speed, aspect and strength of[is differ from body movement. Measurement of anthropometry at this research on course student sit hefty by using one appliance which is special well designed to be used in measurement of human being body criteria, recognized with bench of anthropometer. From result of analysis which had been conducted relied on data test of anthropometry chair dimension and student, at gyration of persentil 5% and 95%. Keyword: Ergonomics, anthropometry, persentil